A mixed-methods study protocol: Perinatal depression screening systems and outcomes in obstetrics clinics - Rachel Vanderkruik; Marlene P. Freeman; Margaret Gaw; Audrey R. L. Reuman; Maya Verghese; Courtney C. Louis; Michael Jellinek; Stephen Bartels; Lee S. Cohen (PLoS ONE, 2025)
Perinatal depression (PND) is an underrecognized and underdiagnosed public health issue with long-term adverse impacts on birthing parents and their children. While obstetrics practices are increasingly encouraged to use existing evidence-based screening tools, there is little data describing the extent to which screening practices and subsequent referrals to care are implemented in clinical settings. The Screening and Treatment Enhancement for Perinatal Depression (STEPS for PPD) study aims to characterize PND screening and referral procedures and identify areas for system improvements. We describe a protocol for an observational study, guided by implementation science frameworks, examining the role of embedded perinatal social workers in managing PND across Mass General Brigham system obstetrics clinics. Our mixed-methods approach integrates qualitative and quantitative data from a variety of sources, including electronic health records, patient-reported surveys, and qualitative interviews, to capture complex screening and referral practices across a large academic medical system. We aim to characterize nuances within the screening and referral system and identify barriers and facilitators to care to inform future hybrid-implementation effectiveness research and improve patient outcomes.